Purchase Intention Determinants of Halal Food in Spain - Mahir Pradana; Syarifuddin Syarifuddin; Haeruddin Hafid; Alini Gilang; Muhammad Diandri (International Journal of Supply Chain Management, 2019)
There have been several research articles focusing on halal food product, but still a few focuses on the Iberian Peninsula region. This study aims to observe society' purchase intention on halal food product in Spain. As an empirical study involving 228 respondents in Spain, this study applies the theory of planned behavior (TPB) using statistical approach of structural equation modeling technique. This study reveals that purchase intention of halal food among Spanish Muslim society are more influenced by the attitude and subjective norm, while behavioral control is not seen as an influential factor in this caseKeywords Halal Food, Halal Marketing, Theory of Planned Behaviour